2016
DOI: 10.1080/03235408.2016.1199177
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of plant-associated proteobacteria isolated from Slovak (Central European) territory

Abstract: a department of general and Quarantine diagnostics, central control and testing institute of Agriculture, haniska, slovakia; b institute of Animal Physiology, slovak Academy of sciences, Košice, slovakia; c faculty of natural sciences, department of chemistry, ABSTRACT Genetic variability of 17 wild strains of γ-proteobacteria isolated from different host plants, locations and seasons, identified via routine diagnostics as Erwinia amylovora, was analysed. The ERIC-PCR confirmed the genetic homogeneity among 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…2). Previous work has shown that Firmicutes and Proteobacteria can promote the growth of plants (Malik et al ., 2016; Qamar et al ., 2017). Our results suggest that the decrease in the relative abundance of Firmicutes and the increase in the relative abundance of Proteobacteria may be the reason for the poor growth and resistance of plants under space microgravity environments.…”
Section: Discussionmentioning
confidence: 99%
“…2). Previous work has shown that Firmicutes and Proteobacteria can promote the growth of plants (Malik et al ., 2016; Qamar et al ., 2017). Our results suggest that the decrease in the relative abundance of Firmicutes and the increase in the relative abundance of Proteobacteria may be the reason for the poor growth and resistance of plants under space microgravity environments.…”
Section: Discussionmentioning
confidence: 99%